2022
DOI: 10.1108/bl-03-2022-0045
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the determinants of ePharmacy services: the moderating effect of technology discomfort

Abstract: Purpose The purpose of this study is to understand the determinants affecting behavioral intention (BI) to use ePharmacy services. The moderating role of technology discomfort in the relationship between BI and the actual use of ePharmacies in the context of Bangladesh is also examined. Design/methodology/approach A descriptive, quantitative approach was used to consider the UTAUT-2 model. Using the convenience sampling method, 255 responses were collected. The data were analyzed using Smart-PLS 3.2 software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…In the fourth paper, Gani, Rahman, Faroque, Sabit and AbdeFattah (2022) analyze the determinants that affect the adoption of e-Pharmacy in behavioral intention and the moderating role of technology discomfort in this relationship. The quantitative results of the analysis of 255 responses using the UTAUT-2 model in the Bangladeshi context revealed that website information, medical care, performance expectation, return policy, social influence, perceived trustworthiness and facilitating conditions are significantly related to the adoption of e-Pharmacy as well as technological-and informational-related resources.…”
Section: Information Systems Science and (New) Technologiesmentioning
confidence: 99%
“…In the fourth paper, Gani, Rahman, Faroque, Sabit and AbdeFattah (2022) analyze the determinants that affect the adoption of e-Pharmacy in behavioral intention and the moderating role of technology discomfort in this relationship. The quantitative results of the analysis of 255 responses using the UTAUT-2 model in the Bangladeshi context revealed that website information, medical care, performance expectation, return policy, social influence, perceived trustworthiness and facilitating conditions are significantly related to the adoption of e-Pharmacy as well as technological-and informational-related resources.…”
Section: Information Systems Science and (New) Technologiesmentioning
confidence: 99%
“…PLS-SEM is one of the popular data analysis techniques used in the strategic management field (Cho et al , 2022) and is useful for complex models as compared to other techniques. Moreover, PLS-SEM is widely used in recent studies for examining intervening relationships between variables (Gani et al , 2022; Sarstedt et al , 2020). A two-step procedure was followed for analyzing and interpreting the PLS model (Henseler et al , 2015).…”
Section: Results and Findingsmentioning
confidence: 99%
“…Due to the inaccessible contact data of women entrepreneurs for use as a sampling frame in this investigation, researchers were forced to use convenience sampling, which is the practice of gathering data from people who are easily accessible (Huang, 2016). Although convenience sampling results may restrict the generalizability of the findings, there is evidence that this technique is reliable for such investigations and is widely accepted in behavioural and business research (Gani et al , 2022; Peterson and Merunka, 2014; Speak et al , 2018).…”
Section: Methodsmentioning
confidence: 99%